IMPLEMENTASI PEMENUHAN HAK PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN PEMERKOSAAN - Wike Wahyu Trisnawati; Basuki Kurniawan (Prodi Akhwal Syahsiyyah IAIN Sorong, 2023)
The phenomenon of sexual crimes that occur in minors is a very serious crime that is being faced by the State of Indonesia. In Indonesia it is very common for children to become victims of immoral and uncivilized acts. The government issued Government Regulation Number 44 of 2008 concerning Compensation, Restitution and Assistance to Witnesses and Victims, and contained in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims. The government through the regulation explains that this problem is the government's responsibility to provide protection and fulfill the rights needed by rape victims.